2016
DOI: 10.1007/s11011-016-9849-3
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal-induced neuroinflammatory response in in vitro astrocytic cultures and hippocampus of experimental animals

Abstract: Diabetes mellitus is characterized by chronic hyperglycemia and its diverse complications. Hyperglycemia is associated with inflammatory responses in different organs and diabetic patients have a higher risk of developing neurodegenerative disorders. Methylglyoxal is a reactive advanced glycation end product precursor that accumulates in diabetic patients. It induces various stress responses in the central nervous system and causes neuronal dysfunction. Astrocytes are actively involved in maintaining neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Elevated MG seems to increase the expression of astrocyte markers (glial fibrillary acidic protein – GFAP and S100B) and cytokines in astrocyte culture and in vivo , leading to astrogliosis and neuroinflammation (Chu et al, 2016). However, cognitive impairment has also been reported without changes in classical parameters of astrogliosis (Hansen et al, 2016b).…”
Section: The Left Arm and Leg Of Glucose Metabolism Modulate Synapticmentioning
confidence: 99%
“…Elevated MG seems to increase the expression of astrocyte markers (glial fibrillary acidic protein – GFAP and S100B) and cytokines in astrocyte culture and in vivo , leading to astrogliosis and neuroinflammation (Chu et al, 2016). However, cognitive impairment has also been reported without changes in classical parameters of astrogliosis (Hansen et al, 2016b).…”
Section: The Left Arm and Leg Of Glucose Metabolism Modulate Synapticmentioning
confidence: 99%
“…Increased dicarbonyl stress may affect many organs [13]. Experimental data have shown that this mechanism impairs the renal, cardiovascular, and central nervous system function, at least partially independent of hyperglycaemia [19,20,21]. An in vivo model in non-diabetic mice showed that the knockout of glyoxalase-1, modifies glomerular proteins and oxidative stress in a way that leads to an impaired renal function [19].…”
Section: Dicarbonyl Stress In Disease Statesmentioning
confidence: 99%
“…In addition, methylglyoxal increases inflammation, leading to endothelial cell loss that contributes to diabetic cardiomyopathy [22]. The intraperitoneal infusion of methylglyoxal in C57BL/6 mice showed a neuroinflammatory response in astrocytes and the hippocampus, suggesting a methylglyoxal-induced impairment of the central nervous system function [21]. Whether dicarbonyl stress contributes to hepatic or respiratory failure, requires further investigation.…”
Section: Dicarbonyl Stress In Disease Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia leads to cellular adaptation to low oxygen by activation of hypoxiainducible factors (HIFs) and activation of anaerobic glycolysis, which also may drive dicarbonyl production (11). The produced dicarbonyls damage intracellular and extracellular proteins mainly due to arginine modifications and the formation of methylglyoxal derived hydroimidazolone-1 (MG-H1), leading to cell and tissue dysfunction (12), which has been shown to impair organ function (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%